Lifestyle Transformation Of Out-Of-Town Students - Ningrum , Natasya Olivia; Marsa , Yummy Jumiati (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study aims to gain an in-depth understanding of the lifestyle transformation of out-of-town students and its impact on their academic life. Out-of-town students are a vulnerable group prone to behavioral changes due to significant shifts in their social, cultural, and economic environments when leaving their hometowns to pursue higher education in big cities. This study employs a qualitative approach with a phenomenological method to explore the students' subjective experiences in facing the dynamics of living away from home. Data collection was carried out through in-depth interviews, observation, and documentation involving main, key, and supporting informants. The data were analyzed using reduction, presentation, and conclusion-drawing techniques, and their validity was tested through source, technique, and time triangulation. The findings show that out-of-town students experience significant lifestyle changes, particularly in aspects of consumption, fashion, and social interactions. These changes directly or indirectly affect their academic life. Some students experienced a decline in focus and study discipline, while others were able to adapt positively by improving their independence, time management, as well as social and academic skills. Thus, the lifestyle transformation of out-of-town students is dynamic and may serve as either an obstacle or a strength, depending on the individual's adaptive capacity and the support of the existing social environment.